2018
DOI: 10.3892/or.2018.6542
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity relationships of chrysoeriol and analogs as dual c‑Met and VEGFR2 tyrosine kinase inhibitors

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2) and c‑Met are tyrosine kinases, which are involved in the tumorigenesis of various types of cancer. Previous studies have demonstrated that the elevated activation of c‑Met is associated with the drug resistance of VEGFR2 inhibitors. Therefore, dual c‑Met and VEGFR2 kinase inhibitors are expected to overcome VEGFR2 inhibitor resistance and subsequently lead to a superior therapeutic outcome to regular VEGFR2 inhibitors. In the present study, it was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Another important protein, whose function can be regulated by chrysoeriol, is BCRP; in fact, the flavone is able to decrease drastically its efflux activity, reducing multidrug resistance typical of cancer cells [148]. Docking experiments and enzymatic assays have demonstrated that chrysoeriol is able also to bind and inhibit two kinases, VEGFR2 (vascular endothelial growth factor 2) and c-Met, both important for tumor progression and resistance to drugs [149]. 8-chrysoeriol, a derivate of chrysoeriol, can promote apoptosis by binding to the BH3 domain of Bcl2 antiapoptotic proteins, that are highly expressed in cancer cells, blocking their activity and inducing cells death [150].…”
Section: Chrysoeriolmentioning
confidence: 99%
“…Another important protein, whose function can be regulated by chrysoeriol, is BCRP; in fact, the flavone is able to decrease drastically its efflux activity, reducing multidrug resistance typical of cancer cells [148]. Docking experiments and enzymatic assays have demonstrated that chrysoeriol is able also to bind and inhibit two kinases, VEGFR2 (vascular endothelial growth factor 2) and c-Met, both important for tumor progression and resistance to drugs [149]. 8-chrysoeriol, a derivate of chrysoeriol, can promote apoptosis by binding to the BH3 domain of Bcl2 antiapoptotic proteins, that are highly expressed in cancer cells, blocking their activity and inducing cells death [150].…”
Section: Chrysoeriolmentioning
confidence: 99%
“…Structurally, the catalytic domain of VEGFR2, as a bi-lobed structure with a small N-lobe and a large C-lobe, plays a key role in the inhibitory potency of these inhibitors. Specifically, the active site of VEGFR2 consists of the following subregions: hydrophobic region I (encapsulated by the residues Leu840, Phe918 and Gly922), hydrophobic region II (encapsulated by the residues Leu889, Ile892, Val898 and Ile1044) and one linker region (encapsulated by the residues Ala866, Val914, Leu1035 and Cys1045) [45]. As shown in Fig.…”
Section: Research Status Of Vegfr2 Inhibitorsmentioning
confidence: 99%
“…A recent study on CSE and its analogues showed that they inhibited both mesenchymal-epithelial transition factor (c-Met) and vascular endothelial growth factor receptor 2 (VEGFR2) that are involved in tumorigenesis of certain types of cancer. 78 To address cancer drug resistance, further SAR analyzes are needed to guide structural optimizations.…”
Section: Structure-activity Relationships Acacetinmentioning
confidence: 99%